The improvement of the biosphere: a challenge in teacher training - Monné Bellmunt, Alexandra; Porté Porté, Carles (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In teacher training, students are asked to prepare proposals that contribute to the improvement of the Biosphere, considering references such as Democratic Culture, the Sustainable Development Goals and circular economy initiatives. The elaboration process contemplates the detection of a need, the analysis of three existing programs justifying their choice, the description of the key elements and finally the specification of a proposal for their own pedagogical improvement. The resulting proposals go in the direction of educating the school community in awareness to protect and preserve the heritage of Andorra.